Neuordnung des innerstädtischen Bodens: Ein Schlüssel für den erfolgreichen Wiederaufbau zerstörter Stadtzentren nach 1945? - Nipper, Josef; Nutz, Manfred; Wiktorin, Dorothea (ERDKUNDE, 1994)
The land factor has always played a decisive role in urban development. In business centres in particular it often presented a major hindrance to forward planning intended to do justice to modern requirements. In town centres, which had experienced almost total destruction during World War 11, there was, at least potentially, an opportunity to carry out land reforms likely to create conditions favouring active planning and successful future development. The wish for and the possibility of a reorganization of land use varied greatly from one city to another, however. The case studies of Cologne and Gießen present two examples of fundamentally different approaches to preparing far reconstruction. In Cologne’s main shopping street (the Hohe Straße), there was scarcely any interference with the existing land structure, whereas Gießen carried out a comprehensive transfer procedure. This paper traces the reasons for the different approaches and the effects for the development of the main shopping streets concerned up to the present, in order to set out and evaluate the significance of land reform measures for town centre development in post-war Germany.